ANALYSIS OF FACTORS AFFECTING EXPORTS INDONESIAN COFFEE - Ramadhani, Muhammad Rizki; Husen, Ratna (Journal of Malikussaleh Public Economics, 2024)
This study aims to analyze the Factors Affecting Coffee Exports in Indonesia. The data used in this study is secondary data from 1990-2016 obtained from the Central Statistics Agency (BPS) and the Indonesian Ministry of Agriculture. The data analysis method used is Vector Auto Regression using Eviews Software. The results of the study can be concluded that partially coffee imports have no effect and are positive on coffee exports in Indonesia, partially inflation does not have an effect and negatively affects coffee exports in Indonesia, partially the exchange rate does not have an effect and is positive for coffee exports in Indonesia and partially production does not have an effect and is positive for coffee exports in Indonesia as well as simultaneously the variables of imports, inflation, exchange rate and production also have no effect and positive effect on coffee exports in Indonesia.The suggestion in this study is that it is expected that the government needs to emphasize the Amount of Coffee Production in Indonesia, this is done so that Exports and The Amount of Coffee Production are balanced with each other and increase state income.